Oral Adverse Reactions Caused by Over-the-Counter Oral Agents - Vanja Vucicevic Boras; Vlaho Brailo; Ana Andabak Rogulj; Danica Vidovic Juras; Dragana Gabric; Danko Velimir Vrdoljak (Hindawi Limited, 2015)
Over-the-counter products rarely cause unwanted reactions in the oral cavity. Oral reactions to these agents are not specific and might present with various clinical oral findings. Detailed medical history is a key to the proper diagnosis of these lesions and fortunately other diagnostic procedures are rarely needed. Lesions are usually managed with elimination of the offending agent and with topical steroids. In more severe cases systemic steroids should be applied.